SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMA BLT-DD MENGGUNAKAN METODE AHP DAN SAW BERBASIS WEB - Riska Aprilia -; Riska Aprilia Putri Nabilla (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The problem of poverty in rural areas requires the distribution of social assistance to be carried out precisely on target, one of which is through the Village Fund Direct Cash Assistance (BLT-DD) program. However, the process of determining BLT-DD recipients in Undaan Lor Undaan Kudus Village is still done manually through village deliberations, so that the resulting decisions are often influenced by subjective assessments and have the potential to be less targeted. This study aims to build a web-based Decision Support System using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods to make the process of determining aid recipients more objective, transparent, and structured. The AHP method is used to determine the weight of each criterion through a pairwise comparison process and consistency testing, while the SAW method is used to calculate the final score and determine the ranking of potential aid recipients. The criteria used include age, employment status, health condition, family status, ownership of other social assistance, economic condition, disability, and type of income. The results show that the Consistency Ratio (CR) value is 0.0348 or less than 0.1, so the criteria weighting is declared consistent and can be used in the next calculation process. From the 20 alternative data sets processed, a more objective and measurable ranking of aid recipients was obtained. The NC alternative received the highest preference score of 0.7818, making it the top priority for aid recipients, followed by RU with a score of 0.6728 and M with a score of 0.6316. The developed system can assist village governments in determining BLT-DD recipients more quickly, accurately, objectively, and transparently, allowing aid distribution to better align with the needs of those in need.